2009
DOI: 10.3109/08958370902806159
|View full text |Cite
|
Sign up to set email alerts
|

Irritant and adjuvant effects of gaseous formaldehyde on the ovalbumin-induced hyperresponsiveness and inflammation in a rat model

Abstract: FA may be an irritant as well as serve as an adjuvant for the onset of asthma or asthma-like symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 50 publications
3
22
0
Order By: Relevance
“…Jung et al (2007) reported that FA exposure alone results in an increased count of eosinophils, higher levels of IgE and interleukin (IL)-4, and lung inflammation in mice. Similar results were also found in a rat model (Qiao et al, 2009). When combined with ovalbumin (OVA) sensitization, FA exposure can induce the following: increased serum levels of anti-OVA IgE in a mouse model (Tarkowski and Gorski, 1995); a high ratio (i.e., 10/12) in guinea pigs with positive signs by sensitive pulmonary function testing (Riedel et al, 1996); and, lung histological changes (i.e., pulmonary inflammation, airway remodeling), increased airway resistance, eosinophil infiltration, and increased IL-4 levels in bronchoalveolar lavage fluid (BALF) in rats (Qiao et al, 2009).…”
Section: Research Articlesupporting
confidence: 78%
See 4 more Smart Citations
“…Jung et al (2007) reported that FA exposure alone results in an increased count of eosinophils, higher levels of IgE and interleukin (IL)-4, and lung inflammation in mice. Similar results were also found in a rat model (Qiao et al, 2009). When combined with ovalbumin (OVA) sensitization, FA exposure can induce the following: increased serum levels of anti-OVA IgE in a mouse model (Tarkowski and Gorski, 1995); a high ratio (i.e., 10/12) in guinea pigs with positive signs by sensitive pulmonary function testing (Riedel et al, 1996); and, lung histological changes (i.e., pulmonary inflammation, airway remodeling), increased airway resistance, eosinophil infiltration, and increased IL-4 levels in bronchoalveolar lavage fluid (BALF) in rats (Qiao et al, 2009).…”
Section: Research Articlesupporting
confidence: 78%
“…FA exposure for 6 or 8 h every day lasting 2 or 3 week has been found to successfully establish FA-induced asthma (Riedel et al, 1996;Jung et al, 2007;Qiao et al, 2009). Exposure times that are too long (Fujimaki et al, 2004) or too short (Franco et al, 2006(Franco et al, , 2009(Franco et al, , 2010 may result in different conclusions.…”
Section: Exposure Conditionsmentioning
confidence: 93%
See 3 more Smart Citations